SINERGI MODAL SOSIAL DAN KEPERCAYAAN INSTITUSIONAL DALAM PARTISIPASI POLITIK PEMBANGUNAN DESA - Aludin (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
This study aims to identify and analyze the role of social capital and institutional trust as the main determinants of local political participation in village development planning in Cibinong District, Cianjur Regency. Community political participation is a crucial aspect in ensuring inclusive development; however, the level of engagement often varies due to structural and cultural factors. The research employed an explanatory quantitative method with a cross-sectional survey design involving 100 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that all hypotheses were supported: social capital has a significant positive effect on local political participation and institutional trust. Institutional trust also has a positive effect on political participation and is proven to act as a mediating variable linking social capital and citizen participation. The synergy between social capital and institutional trust is key to creating democratic and sustainable village development planning. Social capital provides the social infrastructure for cooperation, while institutional trust functions as a psychological mechanism that transforms social relational potential into concrete political action.